PEMANFAATAN PELAYANAN PESERTA JAMINAN KESEHATAN DI UPTD PUSKESMAS BLAMBANGAN PAGAR KABUPATEN LAMPUNG UTARA - Atikah Adyas; Vitria Vina Ulandari; Noviansyah Noviansyah (Malahayati Nursing Journal, 2020)
ABSTRACT : UTILIZATION OF HEALTH GUARANTEE SERVICES IN UPTD BLAMBANGAN PAGAR HEALTH CENTER IN NORTH LAMPUNG REGENCY IN 2019Background : JKN is a social insurance that must be followed by all Indonesians but efforts to expand coverage are carried out in stages. Based on the data it is known that BPSJ patient visits in North Lampung District Health Center in 2018 found Kotabumi II Health Center as many as 25,887 patients, Madukoro Public Health Center as many as 18,280 patients, Udik Health Center as many as 11,436 patients and Blambangan Pagar Health Center 9,116 patients, from the visit data showed that Blambangan Health Center was a Puskesmas with the lowest visit in the area in North Lampung Regency. Purpose : This study aims to determine the service utilization of health insurance participants in the UPTD of Blambangan Pagar Health Center in North Lampung Regency in 2019. Methods : Quantitative research with a Cross Sectional approach with a sample of 140 respondents. The sampling technique was accidental sampling. The study was conducted in May-June 2019 at the UPTD Blambangan Pagar Health Center in North Lampung Regency. The data used are primary data which are the results of the questionnaire. Data analysis was univariate, bivariate (chi square) and multivariate.The results showed 69 (49.3%) did not use JKN services, 85 (60.7%) non-productive age, 117 (83.6%) positive attitudes, 77 (55.0%), poor knowledge, 77 (55.0%) basic education, 90 (64.3%) worked, 75 (53.6%) had less income, 72 (51.4%) long time grades, 85 (60.7%) self-financing, 80 (57.1%) negative needs factor. Results : There is a relationship between personal needs (p-value = 0,000 OR value 4,697), financing (p-value = 0,001 OR value 3,405), time value (p-value = 0,042 value OR 2,126), education (p-value = 0,000 OR value 4,904), occupation (p-value = 0,001 value OR 3,843), income (p-value = 0,027 value OR 2,271), age (p-value = 0,000 value OR 4,037), knowledge (p-value = 0,000 value OR 4,288) in utilizing JKN services at the UPTD of Blambangan Pagar Health Center in North Lampung Regency in 2019. Conclusion : Suggestions for improving attitudes to the community that are still negative are related to the services available at the Puskesmas by adopting a promotive effort approach Keywords : Utilization Of Health Guarantee Service.  INTISARI : PEMANFAATAN PELAYANAN PESERTA JAMINAN KESEHATAN DI UPTD PUSKESMAS BLAMBANGAN PAGAR KABUPATEN LAMPUNG UTARA TAHUN 2019  Pendahuluan :  JKN merupakan asuransi sosial yang wajib diikuti oleh seluruh penduduk Indonesia namun upaya untuk memperluas cakupan dilakukan secara bertahap. Berdasarkan data diketahui bahwa kunjungan pasien BPSJ di Puskesmas Kabupaten Lampung Utara tahun 2018 diketahui Puskesmas Kotabumi II sebanyak 25.887 pasien, Puskesmas Madukoro sebanyak 18.280 pasien, Puskesmas Udik sebanyak 11.436 pasien dan Puskesmas Blambangan Pagar sebanyak 9.116 pasien, dari data kunjungan terlihat bahwa Puskesmas Blambangan merupakan Puskesmas dengan kunjungan terendah di wilayah yang ada di Kabupaten Lampung Utara.Tujuan : Penelitian ini bertujuan untuk diketahui pemanfaatan pelayanan peserta jaminan kesehatan di UPTD Puskesmas Blambangan Pagar Kabupaten Lampung Utara tahun 2019.Metode : Penelitian kuantitatif dengan pendekatan Cross Sectional dengan sampel sebanyak 140 responden. Teknik pengambilan sampel Accidental Sampling. Penelitian dilaksanakan pada bulan Mei - Juni  2019 di UPTD Puskesmas Blambangan Pagar Kabupaten Lampung Utara. Data yang digunakan data primer yang merupakan hasil dari kuesioner. Analisis data secara univariat, bivariat (chi square) dan multivariat.Hasil : Hasil penelitian diketahui sebanyak 69 (49,3%) tidak memanfaatkan pelayanan JKN, 85 (60,7%) usia non produktif , 117 (83,6%) sikap positif, 77 (55,0%), pengetahuan kurang baik, 77 (55,0%) pendidikan dasar, 90 (64,3%) bekerja, 75 (53,6%) pendapatan kurang, 72 (51,4%) nilai waktu lama, 85 (60,7%) pembiayaan sendiri, 80 (57,1%) faktor kebutuhan negatif.Kesimpulan: Ada hubungan antara kebutuhan pribadi (p-value = 0,000 nilai OR 4,697), pembiayaan (p-value = 0,001 nilai OR 3,405),  nilai waktu (p-value = 0,042 nilai OR 2,126), pendidikan (p-value = 0,000 nilai OR 4,904), pekerjaan (p-value = 0,001 nilai OR 3,843), pendapatan (p-value = 0,027 nilai OR 2,271), usia (p-value = 0,000 nilai OR 4,037), pengetahuan (p-value = 0,000 nilai OR 4,288) dalam memanfaatkan pelayanan JKN di UPTD Puskesmas Blambangan Pagar Kabupaten Lampung Utara Tahun 2019. Saran peningkatan sikap kepada masyarakat yang masih negative terkait pelayanan yang ada di Puskesmas  dengan melakukan pendekatan upaya promotif. Kata Kunci : Jaminan Kesehatan Nasional, kebutuhan pribadi, pembiayaan, nilai waktu, pendidikan